Social intrapreneurism and all that jazz : how business innovators are helping to build a more sustainable world - Grayson, David, 1955-; McLaren, Melodie, ....-; Spitzeck, Heiko, ....- (Sheffield : Greenleaf Publishing, 2014)
In response to the world's rapidly growing social, economic and environmental challenges, a growing wave of social intrapreneurs are harnessing the power of large companies to create new business solutions to address societal problems. Social Intrapreneurism and All That Jazz reveals how these highly creative social innovators are improvizing alliances across, as well as beyond, their companies to create micro-insurance products for low-income people; offer delivery services to millions of small businesses in slums around the world; develop alternative-energy solutions inside a major gas and oil corporation; partner with a Brazilian community to produce new natural care products; establish a green advertising network within a major media company; apply engineering expertise to help alleviate poverty and much more - all while generating commercial value for their companies.Distilling insights from interviews with social intrapreneurs, their colleagues and experts around the world, the authors bring to life how business can be about more than just maximizing profit. They identify the mind-sets, behaviours and skills that have helped successful social intrapreneurs journey from initial idea to roll-out by their company - and some of the pitfalls.Although their journeys may be lonely at times and require considerable hard work while working against the grain of large conventional businesses, successful social intrapreneurs are, above all, great communicators who inspire others to join them in achieving a higher purpose beyond the realms of conventional business.Drawing on the metaphors of ensemble jazz music-making, the authors describe how woodshedding, jamming, paying your dues, being a sideman, joining and building a band but, above all, listening to what is happening in business and the wider world - are all part of the life of a successful social intrapreneurism project.
Includes bibliographical references (pages 219-227) and index.
Keywords: Social entrepreneurship